MANAJEMEN HALQOH BAHASA DI PONDOK PESANTREN DAARUL UKHUWWAH MALANG: Language Halqoh Management in Daarul Ukhuwwah Islamic Boarding School Malang - Mufidah, Nuril (Uniqbu Journal of Social Sciences, 2021)
Pondok Pesantran Daarul Ukhuwwah Pakis Malang chose the Halqoh Program as a language learning system capable of being an efficient, effective and productive breakthrough. By striving for good governance, Daarul Ukhuwwah Islamic Boarding School is able to support these facilities. Therefore, in this study the researcher focuses on the halqoh management side and its impact on improving Arabic speaking skills which will be examined using a qualitative approach with a case study strategy. For the research results that can be shown are 1) Halqoh Bahsa which is applied to the Daarul Ukhuwwah Islamic Boarding School has 2 levels / classes, for the first level it is called the tamhidi / beginner class which consists of junior high school students from grade 1 to grade 3, while for the level / class 2 is called Al-Mutawassith which is filled in by SMA / MA students. 2) Halaqoh planning is built on the basis of planning which is prepared with the existence of a goal, material, strategy, students and teachers. 3) Organizing the halaqoh is decided by grouping students and dividing murobbi. 4) The implementation of halaqoh is carried out with supervision by the language section and providing motivation in learning. 5) Evaluation practice is carried out periodically, semester and annually. The management of halaqoh itself has a good impact on educational institutions and is felt by santri as mutarobbi and teachers as murobbi.